Peculiarities of complex sentences with object clauses in the texts of mathematical works in the english and french languages - Volkova, Elena Borisovna; Remennikova, Irina Alexandrovna; Vecherinina, Elena Alexeevna (Universidade Estadual Paulista, 2021)
The aim of the article is to study the basic structural and semantic qualities of two-component complex sentences with object clauses functioning in mathematical works in English and French. The works of outstanding modern mathematicians in the field of differential geometry and algebraic topology served as a material for the research. Using the technique of continuous sampling the authors extracted the sentences to be studied. The basic principles of communicative grammar, structural and semantic analysis, as well as statistical methods to process the extracted material, were applied. For the difficult material to be apprehended properly the language of mathematical works must obey some definite syntactical laws. Complex sentences with clear subordination of clauses favor to a great extent the logical consecutive statement of the mathematical text. Having a more complicated structure than simple sentences they are more evident in semantic facilitating apprehension of the information being conveyed. Constructions with object clauses are highly productive among the complex sentences of the inseparable type. As a rule, it is the subordinate clause that contains somewhat new that promotes the advancement of the course of reasoning whereas the main clause is assigned only an auxiliary part. The article covers such important features of the studied sentences as the position and construction of the main and subordinate clauses, their means of connection, morphological and semantic properties of the subordinating word, etc. In the course of analysis of these structures in the two languages, some common features (for example, the absolute predominance of the preposition of the main clause), as well as considerable differences (for example, the absence of a conjunction in English) are revealed, which should be taken into account at working with the texts of mathematical works in these languages.